2014
DOI: 10.1590/s0080-6234201400005000004
|View full text |Cite
|
Sign up to set email alerts
|

Self-perceived health and clinical characteristics in young adult students from the brazilian northeast

Abstract: Health perception was often optimistic, being important to identify devices to be worked closer to their perception of their actual health condition, increasing the effectiveness of health promotion activities undertaken by professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 9 publications
1
9
0
5
Order By: Relevance
“…A pre-test was conducted at the same time to identify the feasibility of the form, which did not require changes. For the identification of risk, an observation of the environment was conducted and a checklist was completed [7], with the consent of the caregiver. The variables were investigated as three large blocks relative to domestic risk factors: 1) socioeconomic and demographic profile of caregivers and characteristics of the accident; 2) Risk factors relative to infrastructure / household environment; 3) Risk factors relative to the arrangement of objects and furniture in the household.…”
Section: Discussionmentioning
confidence: 99%
“…A pre-test was conducted at the same time to identify the feasibility of the form, which did not require changes. For the identification of risk, an observation of the environment was conducted and a checklist was completed [7], with the consent of the caregiver. The variables were investigated as three large blocks relative to domestic risk factors: 1) socioeconomic and demographic profile of caregivers and characteristics of the accident; 2) Risk factors relative to infrastructure / household environment; 3) Risk factors relative to the arrangement of objects and furniture in the household.…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to study the level of stress and the health risk behaviors among university students, since, as described by Moreira, Santiago and Alencar (18) , the early detection of risk factors can allow planning and implementing intervention programs.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, markers such as satisfaction with work/school (OR=1.34; [0.95;1.90]; p=0.099), self-perception of health Although not remaining in the final model, self-perception of health and satisfaction with body image were significantly associated with overweight, indicating a complex construction of perception of body image. Corroborating this situation, Moreira et al (22) identified an association between nutritional status and self-perception of health in young adult students in a city of Northeastern Brazil. Those who were overweight/obese showed a lower chance of having a positive self-perception of health when compared to the remaining groups.…”
Section: Discussionmentioning
confidence: 98%